2021
DOI: 10.1039/d1nj03893a
|View full text |Cite
|
Sign up to set email alerts
|

The selectivity of a polydimethylsiloxane-based triblock copolymer as the stationary phase for capillary gas chromatography

Abstract: A triblock copolymer (PCL-PDMS-PCL) constructed from polydimethylsiloxane (PDMS) and poly(ɛ-caprolactone) (PCL) chains was synthesized and used as stationary phase for capillary gas chromatography (GC). PCL-PDMS-PCL was statically coated to the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The minimum HETP was 0.31 mm at a flow rate of 0.4 mL/min, corresponding to the column efficiency of 3219 plates/m ( k = 7.21). McReynolds constants were determined to evaluate the polarity of the P6A-C10-2NH 2 column through the injection of five typical probe compounds such as benzene, 1-butanol, 2-pentanone, 1-nitropropane, and pyridine. As described in Table , the P6A-C10-2NH 2 column showed a moderate polarity with an average value of 145, comparable to the commercial HP-35 and DB-17 columns, higher than that of the nonpolar HP-5 column, and lower than that of the classical polar PEG-20M column. Figure c shows the SEM images of the cross section of the P6A-C10-2NH 2 column, indicating a homogeneous coating with a thickness of about 0.25 μm.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum HETP was 0.31 mm at a flow rate of 0.4 mL/min, corresponding to the column efficiency of 3219 plates/m ( k = 7.21). McReynolds constants were determined to evaluate the polarity of the P6A-C10-2NH 2 column through the injection of five typical probe compounds such as benzene, 1-butanol, 2-pentanone, 1-nitropropane, and pyridine. As described in Table , the P6A-C10-2NH 2 column showed a moderate polarity with an average value of 145, comparable to the commercial HP-35 and DB-17 columns, higher than that of the nonpolar HP-5 column, and lower than that of the classical polar PEG-20M column. Figure c shows the SEM images of the cross section of the P6A-C10-2NH 2 column, indicating a homogeneous coating with a thickness of about 0.25 μm.…”
Section: Resultsmentioning
confidence: 99%
“…[23,24] In our previous works, the triblock copolymers including PCL-PDMS-PCL and PCL-PEG-PCL found that the improving chromatographic performance originated from the addition of PCL block. [25][26][27] However, as with most hydroxy terminated polymeric materials, the relatively low thermal stability of PCL necessitates its functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…Capillary gas chromatography (GC) has been widely used in petrochemical, pharmaceutical, environmental, biochemistry, food and other fields, while the stationary phase is the key of GC analysis because the separation performance and retention behavior of a capillary GC column mostly depend on the chromatographic features of its stationary phase. [1][2][3][4] Currently, polymers, [5][6][7][8] macrocyclics, [9][10][11][12] ionic liquids, 13,14 metal-organic frameworks (MOFs), 15,16 and covalent organic frameworks (COFs) 17,18 have been reported as stationary phases for GC separations. It is worth noting that polymers are the most popular chromatographic stationary phases because of their excellent physicochemical properties such as good film-forming properties, chemical stability and easy modification.…”
Section: Introductionmentioning
confidence: 99%